The enjoyment of music an introduction to perceptive listening - Forney, Kristine (W. W. Norton, 2011)
Materials of music; Medieval and renaissance music; The Baroque Era; Eighteenth-century classicism; The nineteenth century; Impressionism and the early twentieth century; Music beyond the concert hall; World War II and beyond.